2018
DOI: 10.1590/1806-90882018000500002
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Effects on Eucalyptus Pellita F. Muell Productivity in the Colombian Orinoco Region

Abstract: The Orinoco region, is the one with the largest area for forest development. Nonetheless, some of its soils are acid and characterized by low fertility levels, which has considerably limited plantation productivity. Therefore, this study aimed at assessing the effects of soil fertilizing and liming by using phosphorus and potassium on 34-month-old Eucalyptus pellita productivity. Tests have been carried out at: Villanueva, Casanare; Puerto Lopez, Meta and La Primavera, Vichada, under a random block design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…It indicated that the eucalypts species in this site is very responsive to the availability of phosphorus in soil (Crous et al, 2015;Tng et al, 2014;Wirabuana et al, 2020). Many references also confirmed that phosphorus is the primary nutrient needed by eucalyptus (Amezquita et al, 2018;Bassaco et al, 2018;Wirabuana et al, 2019), especially in acid soil with low availability of phosphorus (Wang et al, 2015). Several previous studies in other locations also documented that the practice of phosphate fertilizer provides a positive effect on the eucalypts productivity (Gotore et al, 2014;Melo et al, 2016;Wirabuana et al, 2020).…”
Section: Resultsmentioning
confidence: 52%
“…It indicated that the eucalypts species in this site is very responsive to the availability of phosphorus in soil (Crous et al, 2015;Tng et al, 2014;Wirabuana et al, 2020). Many references also confirmed that phosphorus is the primary nutrient needed by eucalyptus (Amezquita et al, 2018;Bassaco et al, 2018;Wirabuana et al, 2019), especially in acid soil with low availability of phosphorus (Wang et al, 2015). Several previous studies in other locations also documented that the practice of phosphate fertilizer provides a positive effect on the eucalypts productivity (Gotore et al, 2014;Melo et al, 2016;Wirabuana et al, 2020).…”
Section: Resultsmentioning
confidence: 52%
“…O crescimento do eucalipto observado neste levantamento foi inferior ao encontrado em outros trabalhos com Eucalyptus pellita (Amezquita et al, 2018;Araújo et al, 2021), porém, pode ser considerado satisfatório considerando a produtividade nacional (IBÁ, 2022). O crescimento também foi similar ao observado por Cipriani et al (2018) para os clones GG100 e VM01 em sistema iLPF próximo à área de estudo.…”
Section: Espécieunclassified
“…Seedlings were planted by initial spacing of 3 m x 3 m. Fertilizer NPK with concentration of 15:15:15 was also added to each seedling with a dose of 100 g to increase the availability of nutrients for eucalyptus because the site experiment had a low content of nitrogen, phosphorus, and potassium in the soil. Moreover, several studies reported eucalyptus is highly responsive to phosphorus availability since it was a macronutrient exceptionally required by this plant (Amezquita et al 2018;Bassaco et al 2018;Sadono et al 2021b). To support the early growth of eucalyptus, the application of weed control was also implemented by slashing and chemical spraying at three and six months after planting.…”
Section: Experimental Designmentioning
confidence: 99%
“…In several decades, there are a number of fast-growing tree species developed as plantation forests in the tropics, one of which is eucalyptus. The development of eucalyptus as a major species in plantation forests has been widely conducted in many tropical countries, such as Brazil, Chile, Colombia, Mexico, Thailand, Vietnam, and Indonesia (Aggangan et al 2013;Hakamada et al 2017;Acuña et al 2018;Amezquita et al 2018;Van Bich et al 2019;Wirabuana et al 2020a). Besides having a short rotation period of approximately 5-8 years (Little et al 2018), the quality of eucalyptus wood suits the requirements of industries, such as for construction materials, pulp and paper, plywood, veneer, and furniture (Forrester 2013;Hii et al 2017;Nambiar et al 2018).…”
Section: Introductionmentioning
confidence: 99%